Informe de precios de carne y ganado de la Patagonia [agosto 2023] - Tejeda, Edgardo Oscar; Claps, Leonardo; Marciani, Santiago Nicolas; Villarreal, Patricia; Podgornik, Gabriel; Guitart Fite, Esteban; Bottaro, Hugo; Garcia, Marcos Jesus; La Torraca, Andres Juan; Bain, Ingrid; Pena, Sergio Osvaldo; Schorr, Alan Geoffrey (Centro Regional Patagonia Norte y Centro Regional Patagonia Sur, INTA, 2023)
EEA Esquel